Family Resilience with Mandailing and Minang Ethnic Amalgamated Marriages - Muhammad Zulfa Hidayat; Bulanov, Akdila (BELIEF: Sociology of Religion Journal, 2024)
This research aims to find out how family resilience with Mandailing & Minang ethnic Amalgamation marriages in Jorong Kauman Nagari Tanjung Betung South Rao District Pasaman Regency. Furthermore, it also knows how various cultures are carried out to carry out marriage, both from Mandailing and Minang ethnicities. The survival of amalgamation marriages is encouraged by the factor of good tolerance patterns between the two ethnicities. Mandailing and Minang ethnicities highly uphold the value of tolerance. Where factors that influence survival are economic and cultural factors. In this writing, the researcher uses a qualitative method where researchers try to describe, describe how family resilience in Mandailing and Minang ethnic amaglamation marriages. In collecting data, researchers used interview, observation and documentation methods. The observations used by researchers are participants and unstructured interviews. In this study obtained the results of how tolerance occurs in a community environment with various types of different ethnicities in one location.